Sepsis as an independent risk factor in atrial fibrillation and cardioembolic stroke - Leng, Yiming; Li, Yalan; Wang, Jie; Deng, Peizhi; Wang, Wei; Wu, Jingjing; Wang, Wenjuan; Weng, Chunyan (Frontiers in Endocrinology, 2023)
Abstract Background. Electrolyte balance is an important factor to sustain the homeostasis of human body environment and in sepsis pathogenesis. Many current cohort-based studies have already revealed that the electrolyte disorder may intensify sepsis and induce stroke. However, the corresponding randomized controlled trials did not show electrolyte disorder in sepsis hasve a harmful effect on stroke. Objectives. To examine the association of genetically sepsis-derived electrolyte disorder with stroke risk using meta-analysis and Mendelian randomization. Results. In four studies (182,980 patients), electrolyte disorders were compared with stroke incidence in patients with sepsis. The pooled Odds ratios (OR) of stroke results in 1.79 (95 percent confidence interval, CI: 1.23-3.06; p<0.05), which showed a significant association between electrolyte disorder and stroke in sepsis patients. Furthermore, in order to evaluate the causal association between stroke risk and sepsis-derived electrolyte disorder, a two-sample Mendelian randomization (MR) study was conducted. The genetic variants extracted from a genome-wide association study (GWAS) of exposure data that are strongly associated with frequently used sepsis, were used as instrumental variables (IVs). Based on the IVs' corresponding effect estimates, we estimated overall stroke risk, cardioembolic stroke risk, and stroke induced by large/small vessels from a GWAS meta-analysis with 10,307 cases and 19,326 controls. As a final step to verify the preliminary MR results, we performed sensitivity analysis using multiple types of Mendelian randomization analysis. Conclusion. Our study revealed the association between electrolyte disorder and stroke in sepsis patients, and correlation between genetic susceptibility toof sepsis and increased risk of cardioembolic stroke, hinting that cardiogenic diseases and accompanying electrolyte disorder interference in due course could help sepsis patients get more benefits in stroke prevention. Keywords: stroke, atrial fibrillation, sepsis, electrolyte disorder, cardiogenic diseases, causal effect, meta-analysis